A JWST Project on 47 Tucanae. Overview, Photometry, and Early Spectroscopic Results of M Dwarfs and Observations of Brown Dwarfs - A. F. Marino; A. P. Milone; M. V. Legnardi; A. Renzini; E. Dondoglio; Y. Cavecchi; G. Cordoni; A. Dotter; E. P. Lagioia; T. Ziliotto; M. Bernizzoni; E. Bortolan; et al. (The Astrophysical Journal, 2024)
James Webb Space Telescope (JWST) observations have been demonstrated to be efficient in detecting multiple stellar populations in globular clusters (GCs) in the low-mass regime of M dwarfs. We present an overview, and first results, of different projects that can be explored by using the JWST observations gathered under program GO2560 for 47 Tucanae, the first program entirely devoted to the investigation of multiple populations in very-low-mass stars, which includes spectroscopic data for the faintest GC stars for which spectra are available. Our color–magnitude diagram (CMD) shows some substructures for ultracool stars, including gaps and breaks in slope. In particular, we observe both a gap and a minimum in the F322W2 luminosity function less than 1 mag apart, and discuss which it could be associated with the H-burning limit. We detect stars fainter than this minimum, very likely brown dwarfs. We corroborate the ubiquity of the multiple populations across different masses, from ∼0.1 M _⊙ up to red giants (∼0.8 M _⊙ ). The oxygen range inferred for the M dwarfs, both from the CMD and from the spectra of two M dwarfs associated with different populations, is similar to that observed for giants. We have not detected any difference between the fractions of stars in distinct populations across stellar masses ≳ 0.1 M _⊙ . This work demonstrates the JWST's capability in uncovering multiple populations within M dwarfs and illustrates the possibility to analyze very-low-mass stars in GCs approaching the H-burning limit and the brown-dwarf sequence.